“Specchio hor di Lucifero, hor di Cristo”: Giovan Battista Andreini’s Mary Magdalene and the Debate on Professional Theatre - Laiena, Serena (Quaderni d'Italianistica)

(untitled) (Iter Press, 2021)
Between 1610 and 1652, the professional actor and playwright Giovan Battista Andreini (1576–1654) published six works on the figure of Mary Magdalene. This essay proposes a reading of this corpus of works as a singular attempt by a professional actor to recast his own image by actively engaging with Counter- Reformation thought. At the same time, it deconstructs Andreini’s patent compliance with Tridentine ideals and reveals that a subtle criticism, expediently hidden by the author, lies at the core of these works. In this corpus, Andreini points out the paradox inherent to the oxymoronic perception of professional performers in early modern Italy, especially actresses, who were considered diabolic by some, divine by others. He therefore censures the relativity in assessing their morality.